Association Between Longitudinal Change in Abnormal Fasting Blood Glucose Levels and Outcome of COVID-19 Patients Without Previous Diagnosis of Diabetes - Song, Siwei; Zhang, Shujing; Wang, Zhihui; Wang, Sufei; Ma, Yanling; Ma, Pei; Luo, Huilin; Wang, Mengyuan; Jin, Yang (Frontiers in Endocrinology, 2021)
This study examined the change in fasting blood glucose (FBG) during hospitalization and its impact on the death risk of COVID-19 patients without previously diagnosed diabetes. This retrospective study included COVID-19 participants without previously diagnosed diabetes. A model with low- and high-stable pattern trajectories was established based on the longitudinal change in FBG. We analyzed the clinical features associated with FBG trajectories and risk factors for death by COVID-19. Overall, 230 patients were enrolled; 44 patients died and 87.83% had the low-stable pattern (average FBG: range, 6.63–7.54 mmol/L) and 12.17% had the high-stable pattern (average FBG: range, 12.59–14.02 mmol/L). There were statistical differences in laboratory findings and mortality between the two FBG patterns. Multivariable logistic regression analysis showed that increased neutrophil count (odds ratio [OR], 25.43; 95% confidence interval [CI]: 2.07, 313.03), elevated direct bilirubin (OR, 5.80; 95%CI: 1.72, 19.58), elevated creatinine (OR, 26.69; 95% CI: 5.82, 122.29), lymphopenia (OR, 8.07; 95% CI: 2.70, 24.14), and high-stable FBG pattern (OR, 8.79; 95% CI: 2.39, 32.29) were independent risk factors for higher mortality in COVID-19 patients with hyperglycemia but without a history of diabetes. FBG trajectories were significantly associated with death risk in COVID-19 patients without diabetes.